2021
DOI: 10.7717/peerj.11564
|View full text |Cite
|
Sign up to set email alerts
|

HPV molecular detection from urine versus cervical samples: an alternative for HPV screening in indigenous populations

Abstract: Background Cervical cancer (CC) is the fourth leading cause of death from neoplasms in women and is caused by the human papilloma virus (HPV). Several methods have been developed for the screening of cervical lesions and HPV; however, some socio-cultural factors prevent women from undergoing gynecological inspection, which results in a higher risk of mortality from cervical cancer in certain population groups as indigenous communities. This study aimed to compare the concordance in HPV detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…As expected, we found a higher concordance rate between urine and genital samples for HPV16 and any of other HR-genotype detection than for low oncogenic risk HPV genotype, especially in males. This result was consistent with other published studies [ 8 , 12 , 15 , 20 , 24 ]. It has been reported that high-risk HPV infection may cause more exfoliated cervical cells in urine, and reflected a higher grade of cervical lesions compared with those low oncogenic risk HPV.…”
Section: Discussionsupporting
confidence: 94%
“…As expected, we found a higher concordance rate between urine and genital samples for HPV16 and any of other HR-genotype detection than for low oncogenic risk HPV genotype, especially in males. This result was consistent with other published studies [ 8 , 12 , 15 , 20 , 24 ]. It has been reported that high-risk HPV infection may cause more exfoliated cervical cells in urine, and reflected a higher grade of cervical lesions compared with those low oncogenic risk HPV.…”
Section: Discussionsupporting
confidence: 94%
“…Urinary HPV testing is performed on the basis that urine can be used for the detection of HPV as the epithelial wall of the uterine cervix and/or vagina normally sheds exfoliated cells into the urine and if there is HPV or any other microbial infections, the shredded cells should contain viral genomes virions including genomes of other infectious organisms. Therefore first void urine sampling has been utilized for the detection of HPV by several authors (Bober et al, 2021;Leeman et al, 2017;Torres-Rojas et al, 2021;Vorsters, Van Damme, et al, 2014). A study Nilyanimit et al, (2017) suggests that urine represents a viable substitute for cervical swabs in detecting HPV.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, urine testing faces challenges such as lower HPV load, presence of PCR inhibitors and contaminating pathogens, and possible higher rate of false positives due to HPV infection of the urinary tract or the lower genital tract. Although many studies have shown correlation between HPV detection in cervix and urine, 195,197–203 they were often very discrepant due to diverse methodologies used during sampling, storage, sample preparation, and DNA extraction, and further optimization and standardization is required.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…On the other hand, urine testing faces challenges such as lower HPV load, presence of PCR inhibitors and contaminating pathogens, and possible higher rate of false positives due to HPV infection of the urinary tract or the lower genital tract. Although many studies have shown correlation between HPV detection in cervix and urine,195,[197][198][199][200][201][202][203] they were often very discrepant due to diverse methodologies used during sampling, storage, sample preparation, and DNA extraction, and further optimization and standardization is required. Regarding the blood analysis, most authors focus on the role of HPV circulating DNA as a prognostic biomarker in blood of patients F I G U R E 3 Schematic illustration of the photoelectrochemical biosensor array (PEBA) platform.…”
mentioning
confidence: 99%